PENERAPAN UNSUR DAPAT MERUGIKAN KEUANGAN NEGARA DALAM TINDAK PIDANA KORUPSI - Arif Setiawan; Umar Ma’ruf (UNISSULA Semarang, 2018)
Article 2 and Article 3 of the Law on Corruption should be recognized as the most frequently used article by law enforcement officers in ensnaring corrupt perpetrators who have harmed the State's finances. In the implementation of the element